Digital marketing Strategies for Melon Agri-Tourism Development in Supporting Sustainable Tourism Villages - Laila Wardani; Iwan Kusmayadi; Djoko Suprayetno; Muhammad Ahyar; Eka Agustiani (Pascasarjana Universitas Mataram, 2026)
Community service activities were conducted at Desa Wisata Kebon Ayu with a focus on implementing digital marketing strategies in the development of melon Agri-tourism to support a sustainable tourism village. The urgency of this program was based on the limited ability of tourism managers to utilize digital media as a promotional and marketing communication tool, resulting in the melon Agri-tourism potential not being widely recognized by the public and tourists. In addition, the rapid development of information technology and the growing trend of experience-based tourism require tourism village managers to adapt to more modern, creative, and sustainable marketing strategies. The objective of this activity was to improve the capacity of melon Agri-tourism managers in implementing digital marketing strategies to enhance tourism attractiveness and support the sustainability of the tourism village. The program was implemented using a participatory approach consisting of field observation, needs identification, socialization, training, and mentoring. The training materials included tourism business management, destination branding, social media utilization, digital promotional content creation, and online platform-based marketing strategies. The community service activity in Kebon Ayu Tourism Village generated several positive impacts on melon Agri-tourism managers and tourism village development. The managers became more capable of building a more attractive and informative tourism destination brand. This activity also encouraged the establishment of tourism management practices that are more adaptive to technological developments and tourism market demands. As a result, it is expected to increase tourist visits and provide economic benefits to the local community.